I really absolutely must have glasses - Child, Lauren; Hurst, Bridget; Tiger Aspect Productions (New York : Grosset & Dunlap, 2009)
Lola, who suddenly decides that she needs to have glasses, goes to the optician despite her brother Charlie's doubts that she actually requires them.
"Text based on the script written by Bridget Hurst, illustrations from the TV animation produced by Tiger Aspect"--T.p. verso.
2.2
K-3.
K-3
Keywords: Charlie (Fictitious character : Child) -- Juvenile fiction; Eyeglasses -- Juvenile fiction; Lola (Fictitious character : Child) -- Juvenile fiction; Charlie (Fictitious character : Child) -- Fiction; Eyeglasses -- Fiction; Lola (Fictitious character : Child) -- Fiction; Charlie (Fictional character : Child); Eyeglasses -- Fiction; Lola (Fictional character : Child); Radio and television novels; Picture books for children; Radio and television novels